Obstetrician's attitudes about delivery through cesarean section: A study in hospitals at Mexico City - A. Vallejos Parás; S. Espino y Sosa; L. Jaimes Betancourt; C. Zepeda Tena; D.A. Cabrera Gaytán; L. Arriaga Nieto; G. Valle Alvarado; M. López Cevantes; L. Durán Arenas (Permanyer, 2018)
Objective: To identify the attitudes of medical obstetrician-gynecologists (Ob-Gyn) and its association with the cesarean section rate. Material and methods: We performed a cross-sectional multicenter survey research, 197 Ob-Gyn were surveyed from eight hospitals, between November 2010 and May 2011. Data analysis included descriptive statistics on the general characteristics of Ob-Gyn, We used the χ2 test for bivariate analyses of categorical variables and logistic regression models to associate Ob-Gyn attitudes and percentage of births by cesarean section. Results: The percentage of cesarean sections births expressed by Ob-Gyn surveyed was 59.2%. Ob-Gyn expressed a preference to delivery by cesarean section in 33.5%, 60.9% of the Ob-Gyn considered themselves skillful when attending cesarean deliveries compared against vaginal delivery. Thirty five percent of Ob-Gyn has scheduled a cesarean section for convenience, while 83.8% of Ob-Gyn said that women prefer cesarean births. In the regression model five variables are significantly associated with the Ob-Gyn that perform 30% or more of their cesarean deliveries, among these include: perception that vaginal are safer procedures than cesarean deliveries and that women have right to choose the type of delivery, whether vaginal or cesarean, with an OR = 4.7 and 7.5 respectively. Conclusions: We have shown that attitudes of Ob-Gyn who are associated with cesarean section rate. These attitudes could be related with the increase of the cesarean births. Resumen: Objetivo: Identificar las actitudes de los obstetras-ginecólogos (Ob-Gyn) y su asociación con la tasa de cesáreas. Material y métodos: Se realizó una encuesta multicéntrica transversal a 197 Ob-Gyn procedentes de 8 hospitales, entre noviembre de 2010 y mayo de 2011. El análisis de los datos incluyó estadísticas descriptivas sobre las características generales de los Ob-Gyn. Utilizamos la prueba χ2 para análisis bivariados de variables categóricas, y modelos de regresión logística para asociar las actitudes de los Ob-Gyn y el porcentaje de nacimientos por cesárea. Resultados: El porcentaje de partos por cesárea expresados por los Ob-Gyn encuestados fue del 59,2%. Los Ob-Gyn expresaron una preferencia por el parto por cesárea en el 33,5% de los casos. El 60,9% de los Ob-Gyn se consideraron hábiles cuando asistían a partos por cesárea en comparación con el parto vaginal. El35% de los Ob-Gyn ha programado una cesárea por conveniencia, mientras que el 83,8% de dichos facultativos manifestó que las mujeres prefieren los nacimientos por cesárea. En el modelo de regresión, 5 variables se asociaron significativamente con los Ob-Gyn que realizan el 30% o más de sus partos por cesárea, entre ellas: percepción de que los procedimientos vaginales son más seguros que los partos por cesárea y que las mujeres tienen derecho a elegir el tipo de parto, ya sea vaginal o cesárea, con un OR = 4,7 y 7,5, respectivamente. Conclusiones: Hemos demostrado las actitudes de los Ob-Gyn que están asociadas con la tasa de cesárea. Estas actitudes podrían estar relacionadas con el aumento en los nacimientos por cesárea. Keywords: Cesarean section, Cesarean rates, Attitudes, Mexico, Palabras clave: Cesárea, Tasas de partos por cesárea, Actitudes, México